The transcriptional regulation of pluripotency - Yeo, Jia-Chi (2013)
The defining features of embryonic stem cells (ESCs) are their self-renewing and pluripotent capacities. Indeed, the ability to give rise into all cell types within the organism not only allows ESCs to function as an ideal in vitro tool to study embryonic development, but also offers great therapeutic potential within the field of regenerative medicine. However, it is also this same remarkable developmental plasticity that makes the efficient control of ESC differentiation into the desired cell type very difficult. Therefore, in order to harness ESCs for clinical applications, a detailed understanding of the molecular and cellular mechanisms controlling ESC pluripotency and lineage commitment is necessary. In this respect, through a variety of transcriptomic approaches, ESC pluripotency has been found to be regulated by a system of ESC-associated transcription factors; and the external signalling environment also acts as a key factor in modulating the ESC transcriptome. Here in this review, we summarize our current understanding of the transcriptional regulatory network in ESCs, discuss how the control of various signalling pathways could influence pluripotency, and provide a future outlook of ESC research.